Traumatic injury to the internal carotid artery by the hyoid bone: a rare cause of ischemic stroke - Fernando Peixoto Ferraz de Campos; Marcia Yoshie Kanegae; Vera Demarchi Aiello; Pedro José dos Santos Neto; Tatiane Carneiro Gratão; Erasmo Simão Silva (University of São Paulo, 2018)
Central nervous system (CNS) ischemic events, besides being a common and devastating disease, are accompanied by severe disability and other morbidities. The cause of such events is not always that simple to diagnose, and among the young, a broad spectrum of possibilities should be considered. We present the case of a young man who presented two episodes of CNS ischemia with a 1 year gap between them, which occurred in the same situation while he was walking and carrying a heavy backpack. The second event first presented as a transient ischemic attack followed by a stroke the day after. The diagnostic work-up showed an indentation of the greater cornu of the hyoid bone over the internal carotid artery, which injured the media and intimal layers. At the arterial injury site, a micro thrombus was found, which explained the source of the embolic event to the CNS. The patient was operated on, and the procedure included the resection of the posterior horn of the hyoid bone, the resection of the injured segment of the internal carotid artery followed by carotid-carotid bypass with the great saphenous vein. The postoperative period and the recovery were uneventful as was the 5-month follow-up. We call attention to this unusual cause of stroke and present other cases reported in the literature.